Preface to the Special Issue on Psychometric Methodology - Buško, Vesna (Array, 2009)
It is a great pleasure and an honour to introduce this special issue of the Review of Psychology. The initiative for setting up thematic journal issues dealing with psychometric topics naturally followed the special scientific events organized and held within our biannual international psychological conferences. First of these events was named Contemporary Issues in Psychometrics: Symposium in Honour of Professor Alija Kulenović. This symposium took place a year after the untimely loss of Professor Kulenović, one of the greatest Croatian scholars in psychological science, an outstanding personality, and - on the word of psychology students of him - the legend of the Department of Psychology. The event and its contents were meant to reflect, in some symbolic way, the width of his intellectual interests, and to remind us on the standards of excellence he had in scientific research and professional work in general. Since autumn 2005, four international psychometric symposia were organized as a tribute to Professor Alija Kulenović, three of which being held within 17th, 18th and 19th Ramiro and Zoran Bujas’ Days in Zagreb, and one held within 15th Psychology Days in Zadar. The program of the symposia included rather diverse topics: it encompassed as basic theoretical questions pertaining to classical and modern test theory or relations of psychometric theory to substantive conceptual issues, so specific methodological problems dealing, for instance, with the adequacy of implementation of certain analytic procedures in particular research applications. This special issue is thought to serve as an initiation of a cycle of thematic journal sections or whole issues devoted to psychometric theory, methodology, and applications, stimulated at least partly by the work presented and discussed at the biannual psychometric events. As readers will notice, the present issue gathered highly interesting and rather sophisticated articles largely focused on methodological questions. The papers include descriptions of simulation studies or research done on real data sets - dealing with essential problems of statistical power and parameter estimation, or presenting demonstrations of various methodological solutions to the problems of psychological measurement, including different aspects of psychometric quality of psychological tests scores. I wish to thank greatly to all the authors and the reviewers of the manuscripts considered for inclusion in this special issue. Their valuable contribution and generous assistance in finalizing the appearance of this journal issue is deeply acknowledged. Several authors as well as reviewers of the articles published in this journal issue took part at least once in our psychometric symposia. We look forward to welcome both them and other authors and experts in the area to this scientific enterprise in the following years. Moreover, we look forward to arranging new thematic journal issues inspired by contributions from previous and the new psychometric events. At the end of this short editorial I would like to note that Professor Alija Kulenović would have indeed very much enjoyed reading and discussing on each of the articles published here. This special issue is dedicated to the memory of him.